2018
DOI: 10.1097/bor.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of stromal cells in chronic inflammatory diseases

Abstract: Stromal cells form the microenvironment of inflamed and diseased tissues. Functional genomics is producing an increasingly detailed view of subsets of stromal cells with pathogenic functions in rheumatic diseases and cancer. Future genomics studies will discover disease mechanisms by perturbing molecular pathways with chemokines and therapies known to affect patient outcomes. Functional genomics studies with large sample sizes of patient tissues will identify patient subsets with different disease phenotypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…These results suggested that Thy-1 might be a potential biomarker for cartilage pathogenesis, degradation, and metabolic turnover [ 97 , 98 ]. Fibroblasts positive for CD90 were enriched in the synovium of RA patients [ 99 ], but only a minority of RA articular chondrocytes displayed a moderate CD90 expression [ 98 ].…”
Section: Chondrocyte Antigens As Potential Targets In Inflammatory Jomentioning
confidence: 99%
“…These results suggested that Thy-1 might be a potential biomarker for cartilage pathogenesis, degradation, and metabolic turnover [ 97 , 98 ]. Fibroblasts positive for CD90 were enriched in the synovium of RA patients [ 99 ], but only a minority of RA articular chondrocytes displayed a moderate CD90 expression [ 98 ].…”
Section: Chondrocyte Antigens As Potential Targets In Inflammatory Jomentioning
confidence: 99%
“…Exposure to inflammation induced by chronic injury, infections, toxins, tissue damage is known to predispose to cancer. OX-S serves to amplify inflammation by activating macrophages and other cells to produce inflammatory peptides [152][153][154][155][156][157][158][159], which disrupt the balance between apoptosis and proliferation in endothelial, vascular smooth muscle, fat, or parenchymal cells. Increased proliferation of adipocytes predisposes to obesity.…”
Section: Agementioning
confidence: 99%
“…During clinically apparent RA, innate and adaptive immune cells invade the synovium and together with jointendogenous cells form tissue-destructive lesions. T cells are key pathogenic drivers required for autoantibody production and sustain synoviocyte proliferation, neoangiogenesis, and cartilage and bone erosions (Slowikowski et al, 2018;Weyand and Goronzy, 2006). Multiple genetic polymorphisms associated with RA risk are implicated in T cell receptor signaling (Fonseka et al, 2017;Terao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%